Ser alguém na vida: condição juvenil e projetos de vida de jovens moradores de um município rural da microrregião de Governador Valadares-MG - Maria Zenaide Alves (2013)
This research addresses two central questions: First, how can we understand the condition of Brazilian youth living in a rural municipality characterized by transnationalism and a migration culture? And, secondly: How do young people in this context organize their life projects? In this dissertation, I argue that the condition of young people in Governador Valadares is marked by social, economic and cultural aspects that reflect hybrid tendencies. These life conditions at times show strong marks of modernity, while also demonstrating strong attachment to traditional society, as they vacillate between global and local cultures. This hybridism is reflected in the life projects of young people who find themselves sometimes divided between traditional and modern values, between the local and the global, between the familial and the individual, and between the advantages and disadvantages of leaving or staying away from large urban centers. I adopted ethnography as a main methodology for this project. To collect the empirical data, the researcher lived during eight months in the rural municipality of São Geraldo da Piedade, in the region of Governador Valadares. The instruments for data collection were direct and participant observation, questionnaires and interviews with high school students. The data were analyzed in light of a multidisciplinary theoretical framework (sociology of youth, sociology of immigration, rural sociology, education and anthropology), with a particular focus on issues affecting youth and their life projects. The research showed that, although there are multiple modes of being young in a rural transnational context, youth in Governador Valadares are strongly influenced by the culture of migration that has been developing in this Brazilian region in recent years and whose main characteristic is a connection to multiple, transnational locales, while retaining an attachment to local. Many of these young people belong to mobile transnational families, as well as the movement of goods, ideas, values and remittances between this mining region and countries like the United States, Portugal and England. The tensions between individual and family projects and between objective and subjective dimensions of the life projects of this group are also discussed in this research. The research showed that young people in São Geraldo da Piedade organize their lives and aspirations according to different models. Although some of these young people did not have clarity about what direction to take in life, they expressed strong concern about the future, voiced in the idea that they know they want to "be someone in life.".